A misosoginia medieval e seus ecos nos Lais de Maria de França - Andrade Filho, Ruy de Oliveira [UNESP]; Carvalho, Lígia Cristina [UNESP] (My University, 2013)
The Lais of Marie de France are a specific type of historical record about the medieval aristocratic society and enables us to decipher the hierarchies that govern the relationship between men and women in the period. As well explains Georges Duby, medieval society tends to present coated with a male character because, among other factors, its latent misogyny. Women were placed under male authority, convinced of their natural superiority , the men despised , mocked her sex , meanwhile feared them, after all, women were Eve’s daughters. So, Lais offer female images that cannot be ignored , since it express the author women’s idea. However , as we seek to demonstrate in this article, Maria of France reflects the representations of the Christian society aristocratic. One note here that this article does not aspire to reach the actual circumstances, but the historical significance of female images present in the Lais.

Os Lais de Maria de França são um tipo específico de registro histórico acerca da sociedade aristocrática medieval e nos possibilita decifrar as hierarquias que regem o relacionamento entre homens e mulheres no período. Como muito bem explica Georges Duby, a sociedade medieval tende a se apresentar revestida de um caráter masculino devido, entre outros fatores, à sua latente misoginia. As mulheres eram colocadas sob a autoridade masculina; convencidos da sua superioridade natural, os homens as desprezavam, zombavam do seu sexo, ao mesmo tempo que as temiam, afinal, eram filhas de Eva. Dito disto, os Lais oferecem imagens femininas que não podem ser desprezadas, posto que expressam a ideia que a autora fazia das mulheres. Entretanto, como procuramos demonstrar neste artigo, Maria de França reflete as representações presentes nesta sociedade aristocrática cristã. Percebe-se aqui que não aspiramos neste artigo alcançar o real vivido, mas o significado histórico das imagens femininas presentes nos Lais.
Medieval Misogyny and its echoes in the Lais of Marie de France
Keywords: Misogyny; Chivalric literature; Maria of France; Female images; Misoginia; Literatura cavaleiresca; Maria de França; Imagens femininas